Generalized Dystonia as Presenting Feature of Wilson Disease: A Case Report - Akansha Anushree MBBS; Sudesh Kumar MD; Piyali Bhattacharya MD; Siddharth Tripathi MBBS; Nandita Chattopadhyay DNB (SAGE Publishing, 2023)
Wilson disease is a rare autosomal recessive genetic disease, caused by the mutation of the ATP7B gene leading to decreased secretion of serum ceruloplasmin in blood and decrease biliary excretion of copper leading to toxic level accumulation in the liver, brain, kidney, and cornea, resulting in development of characteristic liver disease and neuropsychiatric symptoms. Our case presented with mainly clumsiness and gait abnormality without any psychiatric component and any history of liver disease. A 13-year old male, born out of non-consanguineous marriage, presented with clumsy walking and slurring of speech. The child also complained of poor handwriting and slipping of slipper from foot, without any history of abnormal behavior and poor scholastic performance. On examination gait was abnormal with sidewise swaying, increased muscle tone with rigidity and bilateral flexor plantar reflex. Slit lamp examination of eyes revealed bilateral Kayser-Fleischer rings. Serum ceruloplasmin was low (0.03 g/L) and 24-hour urinary copper was high (119.64 μg/day). MRI brain showed B/L putamen hyperintensity and panda sign suggestive of Wilson disease. After the diagnosis of Wilson disease was made, patient was treated with penicillamine and zinc. Child was also followed-up and re-examination showed slight improvement. Though not rare, Wilson disease is an uncommon entity with varied presentations and disabling consequences. Hence high index of suspicion and clinical correlation is required to diagnose it. Early initiation of treatment and good compliance ensure a better outcome.